Serum levels of circulating microRNA-107 are elevated in patients with early-stage HCC. - Sven H Loosen; Mirco Castoldi; Markus S Jördens; Sanchary Roy; Mihael Vucur; Jennis Kandler; Linda Hammerich; Raphael Mohr; Frank Tacke; Tom F Ulmer; Ulf P Neumann; Tom Luedde; et al. (PLoS ONE, 2021)
Background Early detection of hepatocellular carcinoma (HCC), the most common primary liver malignancy, is crucial to offer patients a potentially curative treatment strategy such as surgical resection or liver transplantation (LT). However, easily accessible biomarkers facilitating an early diagnosis of HCC as well as a reliable risk prediction are currently missing. The microRNA(miR)-107 has recently been described as a driver of HCC in both murine and human HCC but data on circulating miR-107 in HCC patients are scarce. In the present study, we evaluated a potential diagnostic and/or prognostic role of circulating miR-107 in patients undergoing tumor resection or LT for early-stage HCC. Methods The Kmplot bioinformatic tool was used to query publicly available databases (including TCGA, GEO and EGA) in order to analyse the prognostic value of tumoral miR-107 expression in HCC patients (n = 372). Serum levels of miR-107 were measured by qPCR in n = 45 HCC patients undergoing surgical tumor resection (n = 37) or LT (n = 8) as well as n = 18 healthy control samples. Results were correlated with clinical data. Results A high tumoral expression of miR-107 was associated with a significantly better overall survival compared to patients with low miR-107 expression levels (HR 0.69, 95% CI 0.48-0.99, p = 0.041). In addition, serum levels of miR-107 were significantly higher in HCC patients when compared to healthy controls. However, miR-107 serum levels in HCC patients were independent of different disease etiology, tumor stage or tumor grading. HCC patients with baseline miR-107 expression levels above a calculated ideal prognostic cut-off value (9.82) showed a clear trend towards an impaired overall survival (p = 0.119). Conclusion Tumoral miR-107 expression levels are a potential prognostic marker in early stage HCC. Furthermore, we describe a potential role of circulating miR-107 levels as a diagnostic biomarker in patients with early-stage HCC.